Evidence-based sentencing and scientific evidence - Martínez-Garay, Lucía (Frontiers in Psychology, 2023)
Evidence-based sentencing (EBS) is a new name for an aspiration that has deep roots in criminal law: to apply the sentence most appropriate to each offender's risk of reoffending, in order to reduce that risk as far as possible. This modern version of the traditional sentencing goals of rehabilitation and incapacitation fits into the broader approach of so-called “evidence-based public policy.” It takes the view that the best existing evidence for reducing reoffending are modern structured risk assessment tools and claims to be able to achieve several goals at once: reducing reoffending, maintaining high levels of public safety, making more efficient use of public resources, and moving criminal policy away from ideological battles by basing it on the objective knowledge provided by the best available scientific evidence. However, despite the success of this approach in recent years, it is not clear to what extent it succeeds in correctly assessing the risk of individual offenders, nor whether it achieves its intended effect of reducing recidivism. This paper aims to critically examine these two issues: the quality of the scientific evidence on which EBS is based, and the available data on the extent to which it achieves (or does not achieve) its intended goals.